2012
DOI: 10.1021/ac3006473
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus-Membrane Fusion Triggered by Proton Uncaging for Single Particle Studies of Fusion Kinetics

Abstract: We report a method for studying membrane fusion, focusing on influenza virus fusion to lipid bilayers, which provides high temporal resolution through the rapid and coordinated initiation of individual virus fusion events. Each fusion event proceeds through a series of steps, much like multi step chemical reaction. Fusion is initiated by a rapid decrease in pH that accompanies the `uncaging' of an effector molecule from o-nitrobenzaldehyde, a photoisomerizable compound that releases a proton to the surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 51 publications
(132 reference statements)
2
51
0
Order By: Relevance
“…Both cholesterol and sphingomyelin in the host-cell membrane strongly supported CHIKV fusion activity. The single-particle assay indicated that multiple, parallel rate-limiting steps precede hemifusion, a phenomenon described earlier for other membrane-fusing viruses (Brandenberg et al, 2015;Costello et al, 2012;Danieli et al, 1996;Floyd et al, 2008). We propose that these steps arise from the parallel action of several fusion trimers.…”
Section: Introductionsupporting
confidence: 72%
“…Both cholesterol and sphingomyelin in the host-cell membrane strongly supported CHIKV fusion activity. The single-particle assay indicated that multiple, parallel rate-limiting steps precede hemifusion, a phenomenon described earlier for other membrane-fusing viruses (Brandenberg et al, 2015;Costello et al, 2012;Danieli et al, 1996;Floyd et al, 2008). We propose that these steps arise from the parallel action of several fusion trimers.…”
Section: Introductionsupporting
confidence: 72%
“…A planar target bilayer of controlled lipid composition is formed on a glass support and can be designed to incorporate lipid or proteinaceous receptors and a lipid-coupled pH-sensitive fluorescent probe. Synchronous acidification is achieved in a microfluidic channel by flowing in low-pH buffer [96], by light-induced liberation of caged protons [97] or by pre-mixing [98]. Using TIRF-M, low-background and high-contrast fluorescence signals are extracted to monitor particles rolling along the bilayer and to visualize arrest, hemifusion and opening of a pore ( Figure 3A).…”
Section: Experimental Design Of Single-particle Viral Fusion Assaysmentioning
confidence: 99%
“…Single-particle experiments on influenza viral fusion showed that the waiting times between decrease of the pH and the cessation of rolling, and hemifusion and pore formation events showed rise-and-decay behavior, suggesting that these processes involve multiple steps [61,88,96,97,100]. The powerful combination of single-particle experiments and analytical [101] and numerical [61] modeling has resulted in a picture in which fusion is the result of a number of HAs acting in a parallel, stochastic fashion, whose proximity allows their stochastic activity to result in a level of coordination needed to overcome the large energetic barriers associated with fusion.…”
Section: Experimental Design Of Single-particle Viral Fusion Assaysmentioning
confidence: 99%
“…TfRs were dialyzed overnight in PBS and concentrated using a 10-kDa Amicon Ultra-15 centrifugal filter unit (EMD Millipore). Purified TfR-eGFP was loaded on top of a supported lipid bilayer (SLB), formed inside a microfluidic device as described elsewhere (15,16). A detailed schematic view of the SPT experimental setup is shown in Fig.…”
mentioning
confidence: 99%